2020
DOI: 10.1007/s12031-020-01563-2
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Chronic Mild Stress and Venlafaxine on the Expression and Methylation Levels of Genes Involved in the Tryptophan Catabolites Pathway in the Blood and Brain Structures of Rats

Abstract: A growing body of evidence suggests that depression may be associated with impairment of the tryptophan catabolites (TRYCATs) pathway. The present study investigated the effects of the chronic administration of venlafaxine on the expression and methylation status of Katl, Tph1/2, Ido1, Kmo and Kynu in the brain and blood of rats exposed to the CMS model of depression. The rats were subjected to the CMS procedure for 2 or 7 weeks and administered venlafaxine (10 mg/kg/day, IP) for 5 weeks. mRNA and protein expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 78 publications
2
9
0
2
Order By: Relevance
“…The regulation of the ephrin-Eph-c-Abl axis by PTPRJ plays a vital role in the proper central projection of retinal axons during development [ 53 ]. Wigner et al confirmed that venlafaxine modulated the expression and methylation level of KYNU in brain when rats were exposed to the chronic mild stress model of depression [ 54 ]. The SNP-dietary interactions suggest that PTPRJ and KYNU may play a role in alcohol-induced depression.…”
Section: Discussionmentioning
confidence: 99%
“…The regulation of the ephrin-Eph-c-Abl axis by PTPRJ plays a vital role in the proper central projection of retinal axons during development [ 53 ]. Wigner et al confirmed that venlafaxine modulated the expression and methylation level of KYNU in brain when rats were exposed to the chronic mild stress model of depression [ 54 ]. The SNP-dietary interactions suggest that PTPRJ and KYNU may play a role in alcohol-induced depression.…”
Section: Discussionmentioning
confidence: 99%
“…As well as changes in sensitivity to reward, the application of CMS and escitalopram therapy resulted in changes in the expression and methylation status of promoter regions of genes involved in oxidative and nitrosative stress, as well as the TRYCATs pathway. Similarly, previous animal studies suggest that such disorders may contribute to the development of depression [40][41][42][43]. In addition, patients with depression also demonstrate exacerbation of the oxidative process and insufficient antioxidant response, as well as overproduction of neurotoxic tryptophan metabolites such as quinolinic acid and 3-hydroxykynurenine [44,45].…”
Section: Discussionmentioning
confidence: 76%
“…The regulation of the ephrin-Eph-c-Abl axis by PTPRJ plays a vital role in the proper central projection of retinal axons during development [49]. Wigner et al con rmed that venlafaxine modulated the expression and methylation level of KYNU in brain when rats exposed to the chronic mild stress model of depression [50]. The SNP-dietary interactions suggest that PTPRJ and KYNU may play a role in alcohol-induced depression.…”
Section: Discussionmentioning
confidence: 99%